2015
DOI: 10.1167/tvst.4.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Retinal Photocoagulation Reliably Generates Uniform Subvisible, Mild, or Moderate Lesions

Abstract: Purpose: Conventional retinal photocoagulation produces irregular lesions and does not allow reliable control of ophthalmoscopically invisible lesions. We applied automatically controlled retinal photocoagulation, which allows to apply uniform lesions without titration, and aimed at five different predictable lesion intensities in a study on rabbit eyes.Methods: A conventional 532-nm photocoagulation laser was used in combination with a pulsed probe laser. They facilitated real-time fundus temperature measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Strategies such as micropulse laser have been developed that may minimize tissue damage, especially in the macula. 12,35 Recently, Koinzer and associates 36 demonstrated in an animal model that automatic, temperature-controlled laser photocoagulation can predictably induce subvisible, mild, or moderate lesions without manual power titration. Application of fundus temperature measurements during laser photocoagulation would enable clinicians to perform laser photocoagulation while minimizing damage to retinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies such as micropulse laser have been developed that may minimize tissue damage, especially in the macula. 12,35 Recently, Koinzer and associates 36 demonstrated in an animal model that automatic, temperature-controlled laser photocoagulation can predictably induce subvisible, mild, or moderate lesions without manual power titration. Application of fundus temperature measurements during laser photocoagulation would enable clinicians to perform laser photocoagulation while minimizing damage to retinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although these lesions were mostly funduscopically invisible, damage could be seen by the OCT evaluation in the outer retinal layers. 25 This result demonstrates the possibility of temperature/time guided irradiation control for clinically increasingly important subvisible thermal treatments as published. 13,15 Studies on rabbits and patients showed that OCT lesion classes are suitable as endpoint criteria during photocoagulation.…”
Section: Discussionmentioning
confidence: 59%
“…20 Furthermore, it was shown that the temperature measurement is suitable for an automatic irradiation control by using the measured temperature-dependent optoacoustic pressure amplitudes for a feedback algorithm that shuts off the treatment laser automatically after the desired lesion strength is achieved. 21,24,25 The aim of this work was the further development and investigation of the automatic irradiation time control during photocoagulation toward different degrees of coagulation. Figure 8 shows that for φ A ¼ 1.1 and φ B ¼ 1.12 the lesions are ophthalmoscopically visible on less than 30% of the irradiations.…”
Section: Discussionmentioning
confidence: 99%
“…The probing laser pulses are applied simultaneously with application of a therapeutic laser to detect temperature rise in tissue during the exposure. Precision of this method is on the order of 1 • C, and this feedback is then used to adjust laser power or pulse duration to ensure predictable outcome of photocoagulation (Koinzer et al 2015).…”
Section: Photocoagulationmentioning
confidence: 99%